Raphael Greenberg, Oren Tal & Tawfiq Da̒adli, Bet Yerah III. Hellenistic Philoteria and Islamic al-Ṣinnabra. The 1933–1986 and 2007–2013 Excavations - Mazor, Gabriel (Journal of Hellenistic Pottery and Material Culture, 2018)
Following the first two published volumes (I, II) of the Bet Yeraḥ excavations, dedicated to the Early Bronze Age, the publication of the Hellenistic and Early Islamic strata is presented in volume III. The excavations described in the report were conducted by Naʻim Makhouly in 1933, Benjamin Maisler (Mazar), Moshe Stekelis and Michael Avi-Yonah in 1945–1946, Pesach Bar-Adon and Philip L. O. Guy in 1950–1953, Emanuel Eisenberg and Ora Yogev in 1982, 1985–1986. In 2009 excavations were renewed in the Hellenistic and Islamic remains by the Institute of Archaeology of Tel Aviv University, and in 2012–2013 Yardenna Alexandre of the Israel Antiquities Authority conducted excavations west of the Bet Yeraḥ mound, revealing Islamic-period installations.